Effect of COVID-19 on building construction projects: Impact and response mechanisms. Issue 1 (February 2021) - Zamani, S H; Rahman, R A; Fauzi, M A; Yusof, L M
Abstract: The construction industry plays significant roles in the country's economic development and growth. There would be a domino impact on the economy if any construction projects are being delayed. As the pandemic of COVID-19 had arisen into our global that had affected the construction industry, including building projects. Identifying the underlying problems caused by COVID-19 can provide the best solution to reduce the pandemic's impact. Consequently, emphasizing the impact of COVID-19 and the strategies to address those problems in the building construction industry becomes vital. Thus, this research objective is to identify problems caused by COVID-19 in the building construction industry and mechanisms to reduce COVID-19's negative impact. The data collection involved individual interviews with 20 contractor companies that are engaged in building construction projects. Then, the data is analyzed using the thematic analysis approach. The findings show that COVID-19 is causing operational and financial issues, while financial aids and complete information is needed to overcome those impacts. These findings will help policymakers improve existing strategic plans and create new policies to cope with the circumstances caused by COVID-19 among building construction organizations.